Fenomena Lelang dalam Transaksi Jual Beli : Studi Syarah Hadis - Rizal Faqih Abdul Jabar (Jurnal Penelitian Ilmu Ushuluddin, 2022)
This article discusses the auction phenomenon in buying and selling transactions: a study of syarah hadith. This research is important because of the lack of literature on the syarah hadith about auctions. The purpose of this study is to discuss the syarah of the hadith buying and selling auctions. The method used in this study is the method of syarah hadith by using qualitative research. The results of this study include auctions, the concept of syarah hadith and syarah hadith auctions. The conclusion of this study is the difference of opinion of the scholars in the study of syarah hadith regarding auctions in buying and selling transactions.